Past into present: An anthology of British and American literature - Roger Gower (Longman, 1998)
The book contains a wide range of British and American literature texts arranged in chronological order from the Anglo-Saxon period to the present day. The texts have been chosen to show the rich diversity of English literature from early verse like "Battle of Maldon" to the Romantic poets, from the diaries of Pepys to the modern novel...